Rounding up the usual suspects: a standard target‐gene approach for resolving the interfamilial phylogenetic relationships of ecribellate orb‐weaving spiders with a new family‐rank classification (Araneae, Araneoidea). (2nd May 2016) - Dimitrov, Dimitar; Benavides, Ligia R.; Arnedo, Miquel A.; Giribet, Gonzalo; Griswold, Charles E.; Scharff, Nikolaj; Hormiga, Gustavo
Abstract: We test the limits of the spider superfamily Araneoidea and reconstruct its interfamilial relationships using standard molecular markers. The taxon sample (363 terminals) comprises for the first time representatives of all araneoid families, including the first molecular data of the family Synaphridae. We use the resulting phylogenetic framework to study web evolution in araneoids. Araneoidea is monophyletic and sister to Nicodamoidearank. n. Orbiculariae are not monophyletic and also include the RTA clade, Oecobiidae and Hersiliidae. Deinopoidea is paraphyletic with respect to a lineage that includes the RTA clade, Hersiliidae and Oecobiidae. The cribellate orb‐weaving family Uloboridae is monophyletic and is sister group to a lineage that includes the RTA Clade, Hersiliidae and Oecobiidae. The monophyly of most Araneoidea families is well supported, with a few exceptions. Anapidae includes holarchaeids but the family remains diphyletic even if Holarchaea is considered an anapid. The orb‐web is ancient, having evolved by the early Jurassic; a single origin of the orb with multiple "losses" is implied by our analyses. By the late Jurassic, the orb‐web had already been transformed into different architectures, but the ancestors of the RTA clade probably built orb‐webs. We also find further support for a single origin of the cribellum and multiple independent losses. The following taxonomic and nomenclatural changes are proposed: the cribellate and ecribellate nicodamids are grouped in the superfamily Nicodamoidearank n. (Megadictynidaerank res. and Nicodamidaestat. n. ). Araneoidea includes 17 families with the following changes: Araneidae is re‐circumscribed to include nephilines, Nephilinaerank res., Arkyidaerank n., Physoglenidaerank n., Synotaxidae is limited to the genus Synotaxus, Pararchaeidae is a junior synonym of Malkaridae (syn. n. ), Holarchaeidae of Anapidae (syn. n. ) and Sinopimoidae of Linyphiidae (syn. n. ).